A prospective assessment of polypharmacy induced drug interactions with corticosteroids - Kumar, S; Thakur, P K; Shah, S K (Journal of Chitwan Medical College, 2017)
Drug interaction represents a major problem in day-to-day practice. The incidence of adverse reactions increases almost exponentially as the number of drugs co prescribed rises, and this is in part due to interaction. This study was aimed to study the incidence of polypharmacy induced drug interactions with corticosteroids and their severity. A prospective observational study was carried out in 211 In-patients from various departments of the hospital during 6 months and subjected to statistical analysis. Out of 211 In-patients, 142 (67.3%) were male and 69 (32.7%) were female, A with maximum (44.9%) belonging to geriatric age group. Most of patients were prescribed with more than 6 drugs. The numbers of prescriptions having drug interactions with corticosteroids were 111, with majority (49.5%) of them were from general medicine ward. A total of 154 drug-drug interactions were found among these prescriptions including 124 moderate, 21 major and 9 contraindicated interactions. Most of the prescriptions (75) were having atleast 1 interaction and 28 prescriptions were having 2 interactions. Out of these interactions, 17, 75, and 62 were having excellent, good and fair scientific evidence. Regarding the onset of these drug-drug interactions, 74(48%) were with delayed onset, 43(27.9%) were unspecified and 37(24%) were with rapid onset. Dexamethasone with ciprofloxacin, tramadol, moxifloxacin, diclofenac, pantoprazole, theophylline were the most encountered combinations. A high prevalence of polypharmacy and drug interactions with corticosteroids was identified in our study. Since concurrent drugs can potentiate irreversible adverse effects of corticosteroids, a regular therapeutic intervention is necessary.